A new genus and species of Neotropical Nemobiinae (Insecta: Orthoptera: Grylloidea: Trigonidiidae: Nemobiinae) - Jesus, Fabiene Maria De; Pereira, Marcelo Ribeiro; Rodrigues, Geanne Carla Ripani; Sperber, Carlos Frankl (Zootaxa, 2017)
A new genus and a new species of Neotropical cricket is described: Pepoapua cariacica n. gen., n. sp., occurring in four Atlantic Forest remnants in the states of Bahia and Espírito Santo, Brazil. This new genus is morphologically similar in external characteristics, both male and female genitalia, with two other Neotropical genera of Nemobiinae: Amanayara and Kevanemobius. The combination of the external morphological characteristics, along with male genitalia, characterize a new genus through combination of the following characters: (i) males and females with morphologically similar tegmina; (ii) tegmina reduced, not reaching half of the second abdominal segment; (iii) dorsal field of the tegmina with parallel veins, without stridulatory vein or any specialized area for sound production; (iv) tibia of the first pair of legs without tympanum; (v) tibia of the third pair of legs with seven dorsal spurs, four inner and three outer, the proximo-dorsal inner spur reduced in size and the disto-dorsal inner spur without glandular aspect; (vi) ovipositor with distal portion of the dorsal and ventral valves serrated; (vii) male genitalia without evident bristles or sensillas; (viii) pseudepiphallic median lobe presenting apical and ventral projections.